A comprehensive review of cathode materials for Na–air batteries. (8th March 2023) - Mao, Pengcheng; Arandiyan, Hamidreza; Mofarah, Sajjad S.; Koshy, Pramod; Pozo-Gonzalo, Cristina; Zheng, Runguo; Wang, Zhiyuan; Wang, Yuan; Bhargava, Suresh K.; Sun, Hongyu; Shao, Zongping; Liu, Yanguo
Abstract : In recent years, rechargeable sodium–air batteries have attracted extensive attention and developed rapidly for electrochemical energy storage applications due to low costs, abundance of precursor resources, and high energy density. Abstract : In recent years, rechargeable sodium–air batteries have attracted extensive attention and shown rapid development for use in the field of electrochemical energy storage owing to low costs, abundance of the precursor resources, high theoretical specific capacity, and high energy density, all of which have contributed to making them one of the most promising alternatives to lithium-ion batteries. Despite the numerous advantages, Na–air batteries also face certain challenges, such as poor charge–discharge reversibility at the cathode, formation of sodium dendrites at the anode, and low catalytic activity for oxygen reduction/evolution reactions. Thus, designing efficient and stable air cathode materials is significant for the development and practical application of Na–air batteries. Therefore, this paper aims to review the advances related to the development of air cathodes in Na–air batteries in the last decade. Here, research on the secondary Na–air batteries are briefly summarized and divided into two categories based on their electrolyte composition: organic Na–air batteries and hybrid Na–air batteries. The air cathode materials are reviewed and categorised based on the material type into the following: carbon materials, transition metals and metal oxides, noble metals, perovskites and spinel oxides, metal–organic frameworks and their derivatives, pyrochlore oxides, and other cathode materials. Furthermore, work in previous studies applying in situ spectroelectrochemical techniques, including Infrared spectroscopy, electron spin resonance, UV/Vis spectroscopy, and Raman spectroscopy, to develop the structure-performance correlations and redox reaction mechanisms of Na–air batteries are summarised. Finally, the challenges faced by Na–air batteries and the prospect of future work are discussed in the conclusions. This review is thus expected to provide a comprehensive understanding of the trends and issues related to the development of Na–air batteries for practical industrial applications.